Customer Expectation and Perception of the Service Quality of Dessert Café in Pathumwan District Bangkok - Thanapotivirat, Pornnapa; Homboonyong, Wachiravit; Amornsittinon, Aucharaporn; Patcharapuwadol, Rattanawadee; Hamloha, Nissara (Dusit Thani College Journal, 2020)
The aim of this study is to focus on the level of customers’ expectation and perception of the service quality of a dessert cafe in Pathumwan District, Bangkok. The evaluation for service satisfaction is also investigated in this paper using quantitative research that consists of accidental sampling of 385 customers for the dessert cafe in Pathumwan District. Hypothesis testing is done by comparing the expectations and perceptions for service quality from customers who gained the services of the dessert café. The data analysis of service satisfaction assessments also investigate to find gaps of service quality between perception (P) and expectations (E) calculated by using formula (P-E). The findings show the expectations and perceptions of service quality in the desserts cafe in every aspect, where it was found that the value of P was less by 0.05, which means significantly different at the level of 0.05 from E and that the satisfaction for service quality between perceived (P) and expectations (E) overall, is less than satisfactory.